2018
DOI: 10.1186/s13068-018-1184-y
|View full text |Cite
|
Sign up to set email alerts
|

Boosting of enzymatic softwood saccharification by fungal GH5 and GH26 endomannanases

Abstract: BackgroundSoftwood is a promising feedstock for lignocellulosic biorefineries, but as it contains galactoglucomannan efficient mannan-degrading enzymes are required to unlock its full potential.ResultsBoosting of the saccharification of pretreated softwood (Canadian lodgepole pine) was investigated for 10 fungal endo-β(1→4)-mannanases (endomannanases) from GH5 and GH26, including 6 novel GH26 enzymes. The endomannanases from Trichoderma reesei (TresMan5A) and Podospora anserina (PansMan26) were investigated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Pans Man26A and the GH26 endomannanase from Aspergillus nidulans , Anid Man26A, were shown to have a significant −4 subsite, and to accommodate galactopyranosyl units not only in the −1 subsite, but also in −2 and +1, in contrast to the GH5 counterparts from A. nidulans Anid Man5A and Anid Man5C 2426 . Several fungal GH26 endomannanases were found to have higher initial rates on soluble galactomannans than the tested GH5 endomannanases, with the GH26 endomannanase from Yunnania penicillata, Ypen Man26A, having the highest initial hydrolysis rate, closely followed by Anid Man26A and the GH26 endomannanase from Westerdykella sp , Wsp .Man26A 1 . However, the tested fungal GH26 endomannanases discriminated differently between the soluble mannans 1 , exemplified by the Ypen Man26A and the Wsp .Man26A which both had high initial hydrolysis rates on locust bean gum, but different rates on more heavily substituted galactomannan.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Pans Man26A and the GH26 endomannanase from Aspergillus nidulans , Anid Man26A, were shown to have a significant −4 subsite, and to accommodate galactopyranosyl units not only in the −1 subsite, but also in −2 and +1, in contrast to the GH5 counterparts from A. nidulans Anid Man5A and Anid Man5C 2426 . Several fungal GH26 endomannanases were found to have higher initial rates on soluble galactomannans than the tested GH5 endomannanases, with the GH26 endomannanase from Yunnania penicillata, Ypen Man26A, having the highest initial hydrolysis rate, closely followed by Anid Man26A and the GH26 endomannanase from Westerdykella sp , Wsp .Man26A 1 . However, the tested fungal GH26 endomannanases discriminated differently between the soluble mannans 1 , exemplified by the Ypen Man26A and the Wsp .Man26A which both had high initial hydrolysis rates on locust bean gum, but different rates on more heavily substituted galactomannan.…”
Section: Introductionmentioning
confidence: 93%
“…Several fungal GH26 endomannanases were found to have higher initial rates on soluble galactomannans than the tested GH5 endomannanases, with the GH26 endomannanase from Yunnania penicillata, Ypen Man26A, having the highest initial hydrolysis rate, closely followed by Anid Man26A and the GH26 endomannanase from Westerdykella sp , Wsp .Man26A 1 . However, the tested fungal GH26 endomannanases discriminated differently between the soluble mannans 1 , exemplified by the Ypen Man26A and the Wsp .Man26A which both had high initial hydrolysis rates on locust bean gum, but different rates on more heavily substituted galactomannan. While Ypen Man26A also showed high hydrolysis rate on guar gum, Wsp .Man26A appeared more restricted by the extra galactose substitutions.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…As an example, Agrawal et al have shown that the performance of Cellic CTec2 on acid or alkali pretreated bagasse and rice straw can be boosted by addition of two AA9 LPMOs from the thermophilic fungi Scytalidium thermophilum and Malbranchea cinnamomea [8]. Very recently, von Freiesleben et al have reported that supplementation with GH5 and GH26 mannanases leads to improved saccharification of pretreated lodgepole pine by Cellic CTec3 [367], confirming previous indications concerning suboptimal levels of mannanase activities in Cellic CTec3 for softwood saccharification [61]. As another example, d'Errico et al showed that a Cellic CTec preparation and the β-glucanase preparation UltraFlo possess only low amounts of glucuronoyl esterase activity and that supplementing these products with CE15 glucuronoyl esterases boosts their saccharification efficiency on pretreated corn fiber [77].…”
Section: Spiking Studies To Highlight Enzyme Activities Lacking In Comentioning
confidence: 99%